Celebrating Easter, Christmas and their associated alien fauna. Issue 2 (15th March 2018) - Lauritsen, Malene; Allen, Richard; Alves, Joel M.; Ameen, Carly; Fowler, Tom; Irving-Pease, Evan; Larson, Greger; Murphy, Luke John; Outram, Alan K.; Pilgrim, Esther; Shaw, Philip A.; Sykes, Naomi
ABSTRACT: Easter and Christmas are the most important events in the Christian calendar. Despite their global reach and cultural significance, astonishingly little is known about the festivals' genesis. Equally obscure is our understanding of the animals that have come to be associated with these celebrations – notably the Christmas Turkey and the Easter 'Bunny' (brown hare and the European rabbit). Like Christianity, none of these animals are native to Britain and the timing and circumstances of their arrivals are poorly understood, often obfuscated by received wisdom. This paper firstly refines the bio-cultural histories of the species that, in contemporary Britain, form integral parts of Easter and Christmas festivities. Secondly, we celebrate the non-native species which have played such an important role in the creation of Britain's cultural heritage.